Question If \( B=1-q \) and \( C=3 q-q^{2}-1 \), find an expreasion that equals \( B-C \) in standard
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To find the expression that equals \( B - C \), first we substitute the values of \( B \) and \( C \): \[ B - C = (1 - q) - (3q - q^2 - 1) \] Now, simplify the expression step by step: 1. Start by distributing the negative sign in front of \( C \): \[ B - C = (1 - q) - 3q + q^2 + 1 \] 2. Combine like terms: \[ B - C = 1 + 1 - q - 3q + q^2 \] 3. This simplifies to: \[ B - C = 2 - 4q + q^2 \] Thus, the expression that equals \( B - C \) in standard form is: \[ q^2 - 4q + 2 \]